Demilitarized Status in International Law and the Militarization Problem of the Eastern Aegean Islands - Cüneyt Yüksel; Nesrin Singil (Public and Private International Law Bulletin)
The roots of the current Eastern Aegean Islands problem go back to the middle of the 19th century when Greece gained its independence. The islands are geographically located in close proximity to the Turkish coast. Therefore, the Islands have been subject to many international conventions, including the 1913 London Treaty and the 1913 Athens Treaty based on the Joint Decision of the Six Major Powers of 1914, the 1923 Lausanne Peace Treaty, the 1923 Convention Relating to the Regime of the Straits, the 1936 Montreux Convention Regarding the Regime of the Straits, and the 1947 Paris Peace Treaty. Greece claims the Eastern Aegean Islands’ demilitarized status that these conventions regulate was abolished. As such, Greece engages in activities and actions aimed at violating the demilitarized status of the Eastern Aegean Islands, with these violations observed to have begun increasing. For this reason, Greece’s claims should be evaluated in the context of current issues, and considering the steps Türkiye will take in response to these violations is also essential. This study is organized into three parts: an examination of the Eastern Aegean Islands and the concept of demilitarized status within the framework of international law, the evaluation of the Greek theses regarding the Eastern Aegean Islands, and the evaluation of the concept of demilitarized status of the Eastern Aegean Islands in light of current issues and Türkiye’s options within the framework of international law. The first section examines the Aegean Islands and the history of their sovereignty and then discusses the concept of demilitarized status and the international regulations regarding it in regard to the Eastern Aegean Islands. The second section addresses the Greek theses on a fundamental change of circumstances having occurred regarding the treaties, how the later treaties replace previous treaties, invoking the right to self-defense, and Türkiye’s inability to rely on the 1947 Paris Peace Treaty. The last section evaluates current issues regarding the demilitarized status of the Eastern Aegean Islands in the context of international law.